Adapting to Climate Change in Bangladesh : Stress Tolerant Seeds for Stress-Prone Regions - Ali, Anika; Sircar, Mrinal (World Bank, Washington, DC, 2012)
In the event of global climate change, agriculture will be one of the worst-hit sectors in Bangladesh. Increasing global temperatures, rising sea levels, and melting polar ice caps result in land submergence, salinity intrusion, drought, and so on all of which drastically impact agricultural productivity and therefore food security and the livelihoods of millions of people in the affected regions. Bangladesh, a low-lying deltaic country, is predicted by the international community of experts to be one of the first countries to be affected, and it has already been experiencing serious impacts of climate change. Agriculture in particular is one of the worst-hit sectors. This smart lesson describes the experience of the agribusiness advisory team in Bangladesh, based on a project focused on climate change adaptation and building resilience of the resource-poor farmers.